Odpowiedzi

Najlepsza Odpowiedź!
2009-12-18T16:19:48+01:00
X +y /2 - x/3 = 4 /*12
x - y /2 +y/3 = -3 / * 6

6 * (x + y) - 4x = 48
3 * (x - y) + 2y = -18

6x + 6y - 4x = 48
3x - 3y + 2y = -18

2x = 48 - 6y /:2
3x - y = -18

x = 24 - 3y
3 * (24 - 3y) - y = -18


x = 24 - 3y
72 - 9y - y = -18

x = 24 - 3y
- 10y = - 90 / : (-10)

x = 24 - 3y
y = 9


x = 24 - 3 * 9
y = 9

x = 24 - 27
y = 9

x = -3
y = 9

  • Użytkownik Zadane
2009-12-18T16:21:35+01:00
(x+y)/2 - x/3 = 4 //*6
(x-y)/2+y/3=-3 //*6

3(x+y) -2x=24
3(x-y) +2y = -18

3x+3y-2x=24
3x-3y+2y=-18

x+3y=24
3x-y=-18

x=24-3y
3(24-3y)-y=-18

72-10y=-18
-10y=-18-72
-10y=-90 /:-10
y=9

x=24-3*9=24-27=-3